2007
DOI: 10.1111/j.1439-0396.2007.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extruding the cereal and/or the legume protein supplement of a compound feed on in vitro ruminal nutrient digestion and nitrogen metabolism

Abstract: An experiment was performed to evaluate the effect of extruding the cereal and/or the protein supplement of a compound feed for intensively reared calves on ruminal N metabolism using an in vitro culture system. A conventional compound feed was produced without extruding [treatment non-extruded (NE)], with the cereal blend extruded (CE), with the protein blend extruded (PE) and with both cereal and protein blends extruded (CPE). Four experimental diets, consisted of 0.90 of each experimental compound feed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…The extrusion of both the cereal and protein blend (treatment CPE) caused a reduction in total tract NDF apparent digestibility in agreement with the results obtained with the same diets in continuous cultures (Solanas et al, 2007), and in vivo with intensively reared calves fed the extruded or non-extruded concentrate (Solanas et al, 2005b). In the latter case, the lower digestibility was associated with a sub-clinic acidosis due to rapid carbohydrate fermentation but this was not the case in the in vitro assay, where a constant pH (6.4) was maintained throughout the incubation period.…”
Section: Apparent Digestibility Of Diets and Urine Allatoin Excretionsupporting
confidence: 89%
See 2 more Smart Citations
“…The extrusion of both the cereal and protein blend (treatment CPE) caused a reduction in total tract NDF apparent digestibility in agreement with the results obtained with the same diets in continuous cultures (Solanas et al, 2007), and in vivo with intensively reared calves fed the extruded or non-extruded concentrate (Solanas et al, 2005b). In the latter case, the lower digestibility was associated with a sub-clinic acidosis due to rapid carbohydrate fermentation but this was not the case in the in vitro assay, where a constant pH (6.4) was maintained throughout the incubation period.…”
Section: Apparent Digestibility Of Diets and Urine Allatoin Excretionsupporting
confidence: 89%
“…Nevertheless, in these studies heat treatments were performed at higher temperatures than in the present study, and several authors have found a higher proportion of ruminal undegraded protein as temperature heat treatment increases (Cros et al, 1991;Petit et al, 2002). However, Solanas et al (2007) obtained higher differences in crude protein degradability than those found in this experiment when the same diets (PE and NE) were incubated in continuous culture fermenters (0.612 vs. 0.712, S.E. = 0.0127).…”
Section: Effect Of Extrusion On Chemical Composition Fermentation Kicontrasting
confidence: 83%
See 1 more Smart Citation
“…Proximate chemical compositions of the optimal treatment as well as two commercial corn-based snacks were determined in triplicate according to AOAC methods [27]. Crude fiber was measured by acid-alkaline digestion [28]. Nitrogen free extract (NFE) was calculated as the percentage difference of the sum of protein, fiber, fat and ash content.…”
Section: Chemical Compositionmentioning
confidence: 99%